Smoczy apetyt : opowieść o krakowskiej kuchni (Wydawnictwo Księgarnia Akademicka, 2021)
Krakow, the former seat of Polish kings, the city with great history, culture and tradition, is unusual on the map of Europe also in terms of the art of preparing meals. The title of the European Capital of Gastronomie Culture 2019, given the city in 2018, constitute a proof of this quality. Krakow Pierogi Festival, Obwarzanek Festival, Krakow Zapusty, or city street food which derives from traditional medieval food stalls for townspeople, merchants and students, were a stimulus for Mieczysław Czuma and Leszek Mazan to research, learn and introduce to the reader the culinary city of Krakow in their book entitled Smoczy apetyt [Huge or Dragon’ s Appetite]. This is an extraordinary story about the culinary past and present of the capital of Małopolska [Lesser Poland] region. It is characterised by humour, but also shows great erudition of authors whose knowledge of products, preparation and serving meals, both in the priva cy of Krakow usual homes and at sumptuous royal, magnate or rich bourgeois courts, arouses admiration and recognition. The publication includes a lot of information about inns, taverns and restaurants, but above all about recipes and meals that have been present on Krakow tables for centuries. The authors describe the history of meat products (beef, veal, lamb, mutton, game), fish (traditional but not only Polish carp), vegetables and fruit (from Polish apples, through Hungarian pepper, famous rnirepoix of Queen Bona, to the American tu ber called spud, ta ter or just po tato), warm drinks and alcoholic beverages (tea, coffee, mead, liqueurs, beer, wine).